In vitro and in vivo antibacterial activity of AB206, a new naphthyridine derivative. - Nagate, T (1980)
AB206 (5,8-dihydro-5-methoxy-8-oxo-2H-1,3-dioxolo-4,5-g quinoline 7-carboxylic acid) is a novel antibacterial agent structurally related to nalidixic acid. AB206 has potent antibacterial activity against clinical isolates of gram-negative bacteria and is 4 to 18 times more active than nalidixic acid. AB206 inhibited the growth of Staphylococcus aureus and Pseudomonas aeruginosa, which were resistnat to nalidixic acid. Cross-resistance was not observed between AB206 and various antibiotics, and most bacterial strains resistant to nalidixic acid were susceptible to AB206. AB206 showed bactericidal activity against Escherichia coli, Proteus, Klebsiella pneumoniae, and P. aeruginosa. Chemotherapeutic effects after oral administration of AB206 in mice experimentally infected with E. coli, K. pneumoniae, and Proteus morganii showed that AB206 was two to four times more potent than nalidixic acid.